Can dendrimer based nanoparticles fight neurodegenerative diseases? Current situation versus other established approaches. (January 2017) - Mignani, Serge; Bryszewska, Maria; Zablocka, Maria; Klajnert-Maculewicz, Barbara; Cladera, Josep; Shcharbin, Dzmitry; Majoral, Jean-Pierre
Abstract: For several decades, the treatment of central nervous system (CNS) disorders such as, for instance, Alzheimer's disease (AD), Huntington's disease (HD), and Parkinson's disease (PD) represented an important challenge due to the difficulty in delivering drug molecules and imaging agents to the brain. Two strategies have been developed aimed at achieving the efficient delivery of drugs to the brain: invasive ( e.g., temporary osmotic Blood Brain Barrier (BBB) opening, direct local delivery of nanoparticles with encapsulated CNS drugs etc. ) and noninvasive approaches. As a part of the noninvasive approach among systemic delivery of drug molecules across BBB using nanocarriers, dendrimers represent promising therapeutics agents per se or nanocarriers of CNS drugs and for gene therapies. This original review emphasizes and analyzes the use of dendrimers as promising systems in the treatment of AD and PD, ischemia/reperfusion injury, neuroinflammation including cerebral palsy, neurological injury after cardiac surgery and particularly after hypothermic circulatory arrest, and for retinal degeneration purposes.